Ownership Structure and Firms’ Performance:Evidence from Finance Sector in Malaysia - Siti Mariam, Ismail; Nazaria, Md. Aris; Ahmad Syubaili, Mohamed; Suzila, Mohamed Yusof; Nurul Syuhada, Zaidi (Human Resource Management Academic Research Society, 2020)
Corporate governance is an internal control system that is essential for sustainable growth and continuous improvements to cater the needs of all parties involved, including investors, employees, customers and shareholders. The study of significance of ownership structure to the firms’ performance in Malaysia is not done extensively in Malaysia. This study gives a better understanding on the issue to strengthen such structures. The corporate governance have been used to address the issue of ownership structure. It is stated that corporate governance can reduce the conflict of interest among shareholder and management. This paper examines the relationship between ownership structure variables and firms’ performance using a sample of 14 firms that listed in Bursa Malaysia in finance sector from 2010 to 2014. Firms’ performance is measured using return on assets (ROA) while managerial ownership (MO) and foreign ownership (FO) represents ownership structure variables. The results from random effects model reveal that the variables are insignificant but they have the positive relationship. From these findings, it revealed that managerial ownership has a positive impact on performance supported by numerous research that had been done.